Living the Paradox of Risk: An Approach for Teachers in Democratically Challenging Situations in Education - Rosén, Maria; Arneback, Emma (Philosophical Inquiry in Education, 2021)
This essay elaborates on the notion of risk in relation to democratically challenging situations in education. This refers to situations in which liberal democratic values are potentially challenged, such as in teaching about controversial issues and in moments of expressions of hurtful speech, which can create in teachers an ambivalence for how to act. The essay takes an understanding of risk as holding a plurality, viewing risk as both undesirable and desirable, to be both reduced and embraced. By considering perspectives that implicitly relate to risk in various ways, this essay explores what can be made possible by embracing risk or its reduction in democratically challenging situations. These perspectives envisage tension between different approaches to risk and visualize how risk may be viewed both as possible moments of change and as possible moments of violence. The essay advances the argument that a one-sided approach to risk may thus pose a challenge to the struggle for democracy, arguing instead for a complex approach to risk. Making use of Jonna Bornemark’s work on the “paradox of action,” the essay proposes the viewing of risk as a paradox, spanning our world of action. The paradox formulates a mutual dependence, in which more is required of one side in one moment and more of the other in the next; neither can be neglected. The essay proposes an approach for teachers: “living the paradox of risk,” which is to act in the space between reducing risk and embracing risk in democratically challenging situations.